Bery Engebretsen letter to Robert K. Myers regarding bird sightings, May 29, 1988 - Engebretsen, Beryet al (1988)
Field notes contributed by Bery Engebretsen in a letter to Robert K. Myers. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1988. Epson - sheet feed